The dense web: local governance and popular participation in Revolutionary Cuba - Collins, Lauren B.S. (2018)
Drawing on a range of primary and secondary sources, including Cuban scholarship which has been overlooked by other non-Cuban scholars, this thesis traces the evolution of local government and popular participation from the overthrow of the Batista regime in 1959 to the present day, and in so doing, it exposes multiple sites for participation in the business of local governance which are available to the average Cuban citizen.